2007
DOI: 10.1016/j.ijrobp.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Induction Chemotherapy and the Associated Tumor Response on Subsequent Radiation-Related Changes in Lung Function and Tumor Response

Abstract: Purpose-To assess the impact of induction chemotherapy, and associated tumor shrinkage, on the subsequent radiation-related changes in pulmonary function and tumor response.Methods and Materials-As part of a prospective IRB-approved study, 91 evaluable patients treated definitively with thoracic RT for unresectable lung cancer were analyzed. The rates of RTassociated pulmonary toxicity and tumor response were compared in the patients with and without pre-RT chemotherapy. In the patients receiving induction che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 45 publications
(60 reference statements)
0
12
0
Order By: Relevance
“…9, 1720, 31. For example, we observed that patients with SPECT perfusion defects adjacent to a central mediastinal mass might have improved PFTs following RT 17.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…9, 1720, 31. For example, we observed that patients with SPECT perfusion defects adjacent to a central mediastinal mass might have improved PFTs following RT 17.…”
Section: Discussionmentioning
confidence: 75%
“…Further, since prior analysis demonstrated that patients with large central tumors and adjacent hypoperfusion (based on pre-RT SPECT scan) have a ≈ 50% probability of experiencing improvements in PFTs post RT 17, analysis was repeated excluding these patients. Since there may be surgery- or chemotherapy-associated changes in lung density, the analysis was repeated in subgroups based on pre-RT surgery or chemotherapy 9, 1820. Last, the analysis was repeated using recognized PFT cut-offs (FEV1 < 2L, ≥ 2L; DLCO < 60%, ≥ 60% predicted) 21, since pre-RT PFTs might be considered for clinical decisions in routine treatments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemotherapy has also been previously implicated in causing radiation pneumonitis. 5, 36,42,43 The fusion also extracted female sex and squamous cell histology as being predictive, though less influential than either chemotherapy or the two dose groups ͑Table III͒. Figure 4 appears to suggest that females undergoing pre-RT chemotherapy are more susceptible to radiation injury.…”
Section: Discussionmentioning
confidence: 99%
“…Patient and treatment characteristics are listed in Table I ͑subsets of this patient group have been analyzed previously 36,37 ͒. The patients were typically treated with either anterior-posterior primary beams delivering 40-45 Gy, followed by off-cord parallel opposed boost beams, or multiple noncoplanar, nonaxial beams.…”
Section: Iia Patient Databasementioning
confidence: 99%